Data critique and analytical opportunities for very large Facebook Pages: Lessons learned from exploring "We are all Khaled Said". Issue 2 (7th November 2015) - Rieder, Bernhard; Abdulla, Rasha; Poell, Thomas; Woltering, Robbert; Zack, Liesbeth
This paper discusses the empirical, Application Programming Interface (API)-based analysis of very large Facebook Pages. Looking in detail at the technical characteristics, conventions, and peculiarities of Facebook's architecture and data interface, we argue that such technical fieldwork is essential to data-driven research, both as a crucial form of data critique and as a way to identify analytical opportunities. Using the "We are all Khaled Said" Facebook Page, which hosted the activities of nearly 1.9 million users during the Egyptian Revolution and beyond, as empirical example, we show how Facebook's API raises important questions about data detail, completeness, consistency over time, and architectural complexity. We then outline an exploratory approach and a number of analytical techniques that take the API and its idiosyncrasies as a starting point for the concrete investigation of a large dataset. Our goal is to close the gap between Big Data research and research about Big Data by showing that the critical investigation of technicity is essential for empirical research and that attention to the particularities of empirical work can provide a deeper understanding of the various issues Big Data research is entangled with.